The Effect of Tax Planning, Profitability, and Leverage on Company Value with Company Size as a Moderating Variable (Empirical Study of Manufacturing Companies Listed on the Indonesia Stock Exchange in the Period 2021-2023) - Puspa Intan Shal Syabila; Andy Dwi Bayu Bawono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of tax planning, profitability, and leverage on firm value with firm size as a moderating variable. This study was conducted on manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The data used are secondary data from the company's annual report available on the IDX website. The analysis method applied is multiple linear regression; however, due to heteroscedasticity, handling is carried out using robust regression to ensure more reliable estimation results. The results of this study are expected to provide insight to investors in making investment decisions and to company management to increase company value through tax planning, profitability, and leverage that are managed effectively.